2007
DOI: 10.1097/jom.0b013e31803b94e2
|View full text |Cite
|
Sign up to set email alerts
|

High Job Strain and Ambulatory Blood Pressure in Middle-Aged Men and Women From the Belgian Job Stress Study

Abstract: Within this study, high job strain was an important independent risk factor for higher ambulatory blood pressure at work, at home, and during sleep in a group of men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 54 publications
4
49
1
Order By: Relevance
“…Most of these studies were cross-sectional (N=9) and used ambulatory BP measures (N=9) (tables A and B). All the studies (except reference 44) presenting significant results found a deleterious effect in both BP at work and: (i) at home (133, 139, 151, 181), (ii) over 24 hours (133,175), and (iii) during sleep (133). The effect magnitudes were comparable for all periods.…”
Section: Methodological Characteristicssupporting
confidence: 50%
“…Most of these studies were cross-sectional (N=9) and used ambulatory BP measures (N=9) (tables A and B). All the studies (except reference 44) presenting significant results found a deleterious effect in both BP at work and: (i) at home (133, 139, 151, 181), (ii) over 24 hours (133,175), and (iii) during sleep (133). The effect magnitudes were comparable for all periods.…”
Section: Methodological Characteristicssupporting
confidence: 50%
“…Inconsistent associations have been reported for job control and diastolic BP (DBP). High job control has been found to be associated with high DBP for females using casual BP readings (15), whereas other researchers using ambulatory BP monitoring (ABPM) readings found low job control to be associated with high DBP (8,16).…”
mentioning
confidence: 89%
“…High alcohol consumption has been found to increase BP (36, 37) and is a valid confounding factor in the association between job control and hypertension. Nevertheless, not all researchers adjust for this variable (8,16,35) perhaps owing to alcohol being a causal factor for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…17 These organizations included two public administrations, one company from the secondary sector and one organization from the service sector. People taking medication for elevated BP were excluded from this study, as well as participants with a previous hospitalization for coronary heart disease (including peripheral vascular disease).…”
Section: Methodsmentioning
confidence: 99%